FGF9 inhibition by a novel binding peptide has efficacy in gastric and bladder cancer per se and reverses resistance to cisplatin. (February 2020) - Wang, Jizhong; Tan, Xiangpeng; Guo, Qiuxiao; Lin, Xiaomian; Huang, Yishan; Chen, Liankuai; Zeng, Xiangfeng; Li, Rongzhen; Wang, Heng; Wu, Xiaoping
Graphical abstract: A novel FGF9-binding peptide (P4) isolated from a phage display peptide library has the potentials of antagonizing FGF9-mediated aggressive phenotype and chemoresistance in both gastric and bladder cancer. Abstract: Aberrant over-expressions of FGF9 in gastric cancer (GC) and its high-affinity receptor FGFR3c in bladder cancer (BC) provide possibilities for the treatment of GC and BC via targeting FGF9. In this study, we isolated a novel FGF9-binding peptide (P4) by screening a phage display random heptapeptide library. Sequence comparison showed that P4 shared high homology with the conserved motif in the immunoglobulin-like (Ig-like) domain II∼III (D2-D3) linker of the FGF9 high-affinity receptor (FGFR3c). The interaction between P4 and FGF9 was confirmed by the surface plasmon resonance (SPR) assay. Functional analysis indicated that P4 counteracted FGF9-induced aggressive phenotype, including cell proliferation, migration, and invasion in vitro, as well as suppressed tumor growth in vivovia down-regulation of the MAPKs and Akt cascades. More importantly, we found that FGF9 served as an underlying mechanism of the chemoresistance in GC and BC cells, and P4 could increase the sensitivity to the chemical agent via antagonizing the suppression effects of FGF9 on cell apoptosis. Taken together, our study identified a novel binding peptide for FGF9, which may serve as a potential therapeutic agent for malignant tumors featured by abnormally up-regulation of FGF9.